THE QASHASH AL-QUR’AN: THE STUDY OF THE PROPHET’S PRAYER IN SURAH AL-ANBIYA 83-84 IN THE PANDEMIC CONTEXT - Hamidi, Ali; Nuryansah, Mohamad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Abstract This paper aims to explain the qashash al-Qur'an about Prophet Ayyub (Job) in his fortitude and patience to face the examination, then take lessons and ibrah for the current social context, where the world community, especially Muslims, is experiencing an examination in the form of the arrival of the Covid 19 outbreak. This paper is the result of the library research with the title "Qashash al-Qur'an: The Study of the Prophet Job's Dua in Surah al-Anbiya 83-84 and Its Contextualization in the Pandemic Period". This article tries to provide an overview of the qashash al-Qur'an on the theme of the Prophet Ayyub with a descriptive-analytical method. So that the good values from an ancient story can be reflected or contextualized into the current condition as material for reflection, lessons, and examples. Based on the author's analysis, the study material is presented in the prayer of Prophet Ayyub which refers to Surah al-Anbiya verses 83-84, so that an understanding of the interpretation of the verse is found, then narrates how the attitude and faith of Prophet Ayyub did not waver despite problems, but he increases his sense of patience, always in gratitude and has a good attitude towards Allah SWT in whatever circumstances.